Admiral Nelson: image and icon - Czisnik, Marianne (University of Edinburgh, 2004)
Few figures in British history have caught the public imagination as much and as enduringly as Admiral Nelson. This thesis explores the ways in which Nelson has been interpreted and used for a variety of purposes. A prologue about the public image of Nelson in his lifetime is followed by the two main parts of the thesis, which deal with Nelson as an image and as an icon respectively. The first part of the thesis, about the image of Nelson, examines historical literature. After an introductory chapter about the general development of the writing of biographies about Nelson, six chapters analyse how the most controversial aspects of Nelson's life have been treated since his death in 1805: his acts of disobedience, his actions as a commander, his involvement in the defeat of the Neapolitan revolution in 1799, his relationship with Lady Hamilton, his death and his character. A chapter also explores historical treatments of Nelson in France, Spain and Gennany. The findings of this part lead to the concluding chapter. The second part analyses the iconography that has made use of certain aspects of Nelson. An introductory chapter examines the immediate public reaction to Nelson's death. The following chapters are dedicated to the different forms of iconography, visual as well as literary: monuments; pictures; material artefacts; poems and songs; novels, plays and films; exhibitions; and propagandistic (political as well as commercial) use made of Nelson. In the conclusion the various findings are brought together in order to give an overview of how Nelson as a historic figure, close to British national identity, has been interpreted and used by succeeding generations.
Keywords: History; Military